Philosophy born of massacres. Marikana, the theatre of cruelty: The killing of the ‘kaffir’ - Rozena Maart (Acta Academica, 2014)
This article probes the possibility of the reasons of reason by interrogating the deconstruction of the subject – the Black man subject as policeman, and the Black man subject as miner – upon the grounds set out by the killing of miners at Marikana. The South African press referred to the events of 16 August 2012 as “The Marikana massacre” and reported that not since the Sharpeville massacre of 1960 had such force and brutality been witnessed. Guided by the murder tactics handed over by White policemen, the Black policemen shot Black men,2 one after the other, for no reason other than to assert the authority of the right to kill when wearing a South African police uniform. I call the resulting massacre a theatre of cruelty, which informsmy point of departure for a philosophy born of massacres. This article addresses the salient features of what marks this relationship between the Black man who considers himself a product of postmodernity and post-apartheid, and the Black man who considers himself the miner.